Reflectometry with Polarized Neutrons on In Situ Grown Thin Films. Issue 5 (17th September 2021) - Kreuzpaintner, Wolfgang; Schmehl, Andreas; Book, Alexander; Mairoser, Thomas; Ye, Jingfan; Wiedemann, Birgit; Mayr, Sina; Moulin, Jean-François; Stahn, Jochen; Gilbert, Dustin A.; Gabold, Henrik; Inanloo-Maranloo, Zahra; et al.
Abstract : Originating from the demand for obtaining depth‐resolved magnetization profiles from thin films and heterostructures, polarized neutron reflectometry (PNR) has developed into a unique research tool, which also finds application in the analysis of superconducting or soft matter thin films. While certain in situ sample environments such as gas‐loading or humidity cells were quickly realized after PNR first emerged, preparing and growing thin magnetic films directly in the neutron beam could only be realized in recent years. Herein, a dedicated insight is given on the history and development of in situ thin film growth capabilities for PNR, from early pioneering experiments to the present day. The scientific and technological challenges as well as the advances of neutron sources, neutronics, and data treatment that have led to its realization are highlighted together with the unique research opportunities that it provides and recently obtained experimental results. Abstract : In light of the availability of upcoming high‐brilliance neutron sources and novel optics, the history and development of in situ thin‐ﬁlm growth capabilities for polarized neutron reflectometry are reviewed. Previous challenges and the technological advances of the last years are discussed, with recent experimental results highlighting the unique novel research opportunities that the in situ technique provides.